AFKAR AL-JAMA’AH AL-JIHADIYYAH FI KITAB AL-FARIDAH AL-GHAIBAH: NAZARIYYAT NAQDIYYAH - Sayyed Zuhdi (IAIN Surakarta, 2017)
This article aims to describe the principal ideas of the book Al-Farīḍah Al-Gāibah by Muhammad Abdussalam Faraj which was one of the most important references for the jihadis and extremist. These principal ideas in this book are misinterpreted, especially about jihad in Islam and about other related concepts, such as takfir, al-hākimiyyah, killing Muslim, and method of understanding religious texts. This paper found that the major problem of the author is his excessive enthusiasm towards Islam’s teaching without the proper instruments and without the right method to understand religious texts. Most of the wrong concepts in the book are caused by wrong methods in interacting with verses and prophetic traditions related to legal issues. The most dominant misinterpretation is how the author interprets verses and hadiths partially, without referring to other related texts.